Short-term radiographic results of a cemented polyethylene keeled glenoid component with varying backside radiuses of curvature - Raiss, Patric; Schnetzke, Marc; Bruckner, Thomas (Journal of shoulder and elbow surgery, 2018)
Background: This study analyzed the radiographic results of a cemented all-polyethylene keeled glenoid component available in different sizes and multiple backside radiuses of curvature. Methods: The study group consisted of 118 cases (114 patients). There were 63 women and 51 men. Mean age at the time of arthroplasty was 68 years (range, 51-85 years). True anterior-posterior radiographs obtained postoperatively and at the final follow-up were analyzed for implant seating and the occurrence of radiolucent lines. Glenoid morphology and fatty infiltration of the rotator cuff muscles were examined using computed tomography scans. Mean follow-up was 38 months (range, 24-70 months). Results: The mean radiolucent line score after surgery was 0.54 points (range, 0-3 points), and 90% had no or only 1 radiolucent line. At the final follow-up, the mean score was 1.06 points (range, 0-3 points), and 74% had no or only 1 radiolucent line. The score increased significantly over time (P < .001). No component was at risk for loosening. No correlation was found between patient age, sex, hand dominance, glenoid morphology, or fatty infiltration of the rotator cuff muscles and the occurrence of radiolucent lines. Conclusion: In the short-term, the glenoid component analyzed in this study showed promising radiographic results, with a low number of radiolucent lines without failure. However, the mean radiolucent line score increased significantly over time, and long-term observations are necessary to confirm a possible advantage compared with older component designs.